2013
DOI: 10.1074/jbc.m112.410811
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma-derived Polymeric IgA and IgM Antibodies Associate with Secretory Component to Yield Biologically Active Secretory-like Antibodies

Abstract: Background: Production of SIgA or SIgM for therapeutic application remains an unsolved issue. Results: Human plasma-derived polyclonal, polymeric IgA and IgM associate with recombinant or colostrum-derived human secretory component to form digestion-resistant, functionally active SIgA-and SIgM-like molecules. Conclusion: SIgA and SIgM can be rebuilt ex vivo from plasma-derived IgA/IgM. Significance: This would enable development of SIgA/SIgM-based mucosal therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 48 publications
3
48
0
Order By: Relevance
“…We found that plasma-derived purified pIgA and IgM can associate with a recombinant secretory component (SC) with a 1:1 stoichiometry and that this association delayed the degradation of pIgA or IgM by intestinal washes containing proteases. In addition to these essential biochemical features, we showed that pIgA and secretory-like IgA delayed damage to epithelial polarized Caco-2 cell monolayers induced by a virulent strain of enteropathogenic Shigella flexneri (29). However, how the plasma-derived Ab operates to block the bacterium and contributes to epithelial homeostasis was not addressed in this study.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…We found that plasma-derived purified pIgA and IgM can associate with a recombinant secretory component (SC) with a 1:1 stoichiometry and that this association delayed the degradation of pIgA or IgM by intestinal washes containing proteases. In addition to these essential biochemical features, we showed that pIgA and secretory-like IgA delayed damage to epithelial polarized Caco-2 cell monolayers induced by a virulent strain of enteropathogenic Shigella flexneri (29). However, how the plasma-derived Ab operates to block the bacterium and contributes to epithelial homeostasis was not addressed in this study.…”
mentioning
confidence: 78%
“…Human Plasma pIgA and SIgA Abs Agglutinate Bacteria Lead to a Decrease of the Bacterial Load in Caco-2 Cell Monolayers and of Proinflammatory Cytokines/Chemokines-We demonstrated previously that human plasma-derived pIgA and reconstituted SIgA, but not plasma mIgA, significantly maintained Caco-2 cell intestinal epithelial monolayer integrity after O/N infection with S. flexneri by preventing the reduction of TER, the disruption of the tight junction network, and the detachment of filter-bound Caco-2 cells (29). However, the underlying mechanisms explaining protection were not addressed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations